Palladium-Catalyzed One-Pot Conversion of Aldehydes and Ketones into 4-Substituted Homopropargyl Alcohols and 5-En-3-yn-1-ols† - Umaña, Christian A. (2017)
Sequential treatment of 2,3-dichloropropene with magnesium and n-BuLi generated the equivalent of 1,3- dilithiopropyne, which adds regiospecifically to aldehydes and ketones to produce homopropargyl alcohols. The lithium acetylide intermediate formed in this protocol can be further reacted with aromatic and vinyl halides, under palladium catalysis, to produce 4-substituted homopropargyl alcohols and 5-en-3-yn-1-ols, respectively, in one-pot with good overall yields.